Evaluation of the accuracy of 2D cephalometric analysis in the measurement of bucculingual incisors inclination (Latakia University Journal -Medical Sciences Series, 2024)
Aim: To study the accuracy of angular measurements of incisors in the sagittal plane when measured using lateral cephalometric radiographs and comparing them with measurements made on CBCT images.Materials and Methods This study was designed as a retrospective radiographic study and the study sample included 30 CBCT images of patients with skeletal class I. Three-dimensional cephalometric analysis was used to measure the bucculingual inclination of the incisors from which lateral cephalometric radiographs were derived and the same measurements were repeated.Results: There were no statistically significant differences in the bucculingual inclination values of the incisors measured using 2D analysis on derived cephalometric radiographs when compared with those measured using 3D cephalometric analysis on CBCT radiographs.Conclusions: The study concluded that the accuracy of 2D cephalometric analysis and conventional cephalometric measurements derived from CBCT images were sufficient for measuring the bucculingual inclination of the incisors.